1997
DOI: 10.1017/s0950268897007887
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of varicella vaccination for health care workers

Abstract: A simulation model was constructed to assess the relative costs and cost-effectiveness of different screening and vaccination strategies for dealing with hospital incidents of varicella exposure, compared with current policies, using data from published sources and a hospital survey. The mean number of incidents per hospital year was 3.9, and the mean annual cost of managing these incidents was pounds 5170. Vaccination of all staff would reduce annual incidents to 2.2 at a net cost of pounds 48,900 per inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In particular, Italy's varicella notification data needs to be properly verified. In light of the information available, it would apparently be more productive to limit the use of varicella vaccine to those individuals at risk, as currently recommended in Italy [18], and to verify the epidemiological and costbenefit impact of eventual vaccine campaigns targeting, for example, susceptible women of reproductive age or health-care personnel [28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Italy's varicella notification data needs to be properly verified. In light of the information available, it would apparently be more productive to limit the use of varicella vaccine to those individuals at risk, as currently recommended in Italy [18], and to verify the epidemiological and costbenefit impact of eventual vaccine campaigns targeting, for example, susceptible women of reproductive age or health-care personnel [28].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study may have overestimated the overall burden of disease, especially among persons with underlying conditions who have longer hospitalizations. Nonetheless, there would have been a substantial cost in case management and in hospital epidemiologic considerations for any inpatient case of incidental primary varicella or herpes zoster, especially in a person who was immunosuppressed [32,42]. In the absence of doing chart reviews, similar limitations apply to the data on underlying conditions and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of rising seronegativity in adults independent of country of origin suggests potential cost benefit from adult vaccination programmes in susceptible populations 18. Gray et al found serotesting of adult health care workers with a negative or uncertain history of varicella was the most cost effective approach to vaccination 94. This approach is also supported by mathematical models95 96 and a 1998 cohort study of American soldiers 92.…”
Section: Identified Studies Meeting Inclusion Criteriamentioning
confidence: 91%